Intraoperative portable ultrasonography localization of clinically impalpable soft-tissue tumors - Jagadeesan, Jagajeevan (BioMed Central, 2012)
BACKGROUND: Most soft-tissue tumors are clinically palpable; however, some can be impalpable to clinical examination making it difficult to plan surgical management. METHODS: We present a simple method of perioperative tumor localization using a portable ultrasonography machine. RESULTS: We used the technique for seven cases, on each occasion identifying the tumor and facilitating the optimal surgical approach. CONCLUSION: The technique is reproducible and readily available, and we recommend its use.